KONSEP KEPEMILIKAN HARTA DALAM ISLAM - Fitriana Firdausi (Jurnal Al-Mubarak: Jurnal Kajian Al-Qur'an dan Tafsir, 2026)
The concept of property ownership in Islam differs from that of other systems. Islam, as stated in the Qur’an, teaches that within the wealth possessed by a Muslim lie the rights of others, as mentioned in Surah al-Z{a>riya>t (51:19). But how should we interpret this verse? In fact, in Indonesia, there are many regions with government regulations prohibiting the giving of money to beggars. It is in this context that the author will explore the theme of property ownership and its connection to the “sa>’il” and the “mah}ru>m” in Surah al-Z{a>riya>t verse 19, by applying the “Ma’na Cum Maghza” approach. The choice of this approach is due to the contextual nature of this research, which takes into account contemporary and local contexts. Upon completion of the study, the author concludes that this verse contains a universal command from Allah to assist others, both materially and non-materially. As for the method and distribution of aid, particularly material aid, it may be provided directly to those in need (sa>’il and mah}ru>m) or channeled through social institutions, as exemplified by Caliph Umar bin al-Khattab and stipulated in several Regional Regulations in Indonesia.